A simple and green analytical method for determination of copper(ii) in whisky and sugarcane spirit by diffuse reflectance spectroscopy. Issue 8 (10th February 2016) - Carlos de Souza, João; Pezza, Helena Redigolo; Pezza, Leonardo
Abstract : In this paper we propose a new, fast, simple, economical, portable and environmentally friendly analytical methodology for the determination of copper(ii ) ions in whisky and sugarcane spirit, using the combination of spot-test and diffuse reflectance spectroscopy. Abstract : In this paper we propose a new, fast, simple, economical, portable and environmentally friendly analytical methodology for the determination of copper(ii ) ions in whisky and sugarcane spirit, using the combination of spot-test and diffuse reflectance spectroscopy. The method is based on the reflectance measurements at 559 nm, of the complex formed from the spot test reaction between the copper(ii ) ions with the chromogenic agent 1-(2-pyridylazo)-2-naphthol (PAN), using filter paper as the solid support. The best conditions for the reaction occurred with the addition of 30 μL of a PAN solution at a concentration rate of 0.12% m/v in ethanol and 30 μL of an alcoholic solution of copper(ii ) ions at 40.0% v/v with pH 5.00 and 5 minutes of reaction time. The following elements were found to interfere in the reaction process – iron(iii ), nickel(ii ), cobalt(ii ), cadmium(ii ), manganese(ii ), zinc(ii ) and lead(ii ) ions. Malonic acid and sodium triphosphate at a concentration of 0.25% m/v were therefore used as masking agents, which contributed towards the reduction of the magnitude of the interference effect from around 20.3% to approximately 2.0%. Under optimized conditions for the determination of copper(ii ), the analytical curve obtained could be described by: ΔAR = 0.0121 C Cu(ii ) + 0.0038 ( R 2 = 0.9982). Linearity was obtained up to a concentration of 10.0 mg L −1 of copper(ii ), and limits of detection and quantification (calculated using the standard deviation of the blank) were 0.12 and 0.47 mg L −1 of copper(ii ), respectively. The proposed method was applied for the determination of copper(ii ) ions in samples of whisky and sugarcane spirit and the results were compared with those obtained by the official method with a 95% level of confidence.